Characterization and adsorption performance of waste-based porous open-cell geopolymer with one-pot preparation. Issue 9 (1st May 2021) - Ji, Zehua; Su, Liya; Pei, Yuansheng
Abstract: Porous geopolymer foams are promising lightweight materials combining strong strength and adsorption properties. A waste-based porous open-cell geopolymer (POG) was synthesized by one-pot method and investigated in terms of unconfined compressive strength (UCS), pore distribution and adsorption ability. This paper investigates the effect of preparation conditions (raw materials and stabilizing/foaming agents proportion, modulus, curing temperature) on the performance of POG. Results indicated that POG was successfully prepared by industrial wastes (blast furnace slag, BFS) and municipal wastes (water treatment residue, WTR). The appropriate range of conditions were determined for the preparation of POG (H2 O2 = 1.50 2.50 wt%, K12 = 1.50 2.00 wt%, modulus = 1.25 2.00, and temperature = 60 70 °C). Under these conditions, the UCS in the range 1.77 4.77 MPa, and the total porosity in the range 35.19 69.97 vol%. The extreme environments resulted in the form of instable structure and discontinuous pore structure. The statistical results demonstrated that the total porosity, mean diameter, and max diameter of POG are significantly negative correlated with UCS, and the relationship of total porosity and UCS can be described by Ryshkevith (R 2 =0.8459) and Schiller model (R 2 =0.8689). Compared to the geopolymer bulk, POG showed significant adsorption advantage for heavy metal cations and cationic dyes, and the adsorption removal rates of POG for Cd 2+, Cu 2+, Pb 2+, and MB rising to 92.25%, 119.80%, 110.77%, and 163.98%, respectively. The adsorption mechanisms are mainly based on the negative charge of [AlO4 ] - tetrahedron and cation exchange between heavy cations and Na + or Ca 2+ in internal matrix. This study indicated that the BFS and WTR are feasible solid wastes for the fabrication of POG, which can be applied in the filtration and adsorption fields for contaminants removal. Highlights: A waste-based porous open-cell geopolymer (POG) was prepared by one-pot method. The appropriate range of preparation conditions were determined for POG. Relationship between structural parameters of POG were analyzed by statistics. The reuse of solid wastes as raw material enhances waste potential valorization.